Dimension social del dialogo del FMI en materia de politicas : Preparado por el personal del Fondo Monetario International. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1995)
Dimension social del dialogo del FMI en materia de politicas.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Foreign Exchange; International Agreements and Observance; International Organizations